Numerical evaluation of urban geometry's control of wind movements in outdoor spaces during winter period. Case of Mediterranean climate - Bouketta, S.; Bouchahm, Y. (Renewable energy, 2020)
The impact of urban geometry on thermal comfort in outdoor spaces has been the subject of several studies, but few of them have addressed the control of adverse wind effects in urban humid areas. This work deals with this specific context. It aims to highlight the role of the geometry of urban spaces in the control of the wind, more particularly the “prospect” H/w, in the city of Jijel (Algeria), where wind is the essential element to be reckoned with. It is shown concretely into in-situ measurement campaigns during which microclimatic parameters were recorded simultaneously for tow case studies with distinct geometries spaces between the U-shaped and L-shaped buildings. More precisely, the first step is to identify the most important geometrical parameters and then describe the wind behavior by numerical simulation with the help of the “Envi-met V4” software (licenced). The results show the impact of this geometrical indicator reputed to have a great influence on wind flow, which has the main impact on urban ventilation and must be taken into account in order to control the wind. •Geometry of outdoor space has a significant impact on wind flow and takes part in controlling it.•H/w ratio is the most important parameter which has a great influence on wind flow.•Wind incidence can play a significant role in canalizing or blocking the wind.•Space between buildings has to be calculated in connection with the wind incidence.•U and L geometric forms have created badly ventilated enclosed spaces.